PEMBUATAN APLIKASI PERIKLANAN SUSUNAN ACARA KEGIATAN UPACARA TRADISIONAL TABOT DI BENGKULU - Rizka Tri Alinse; Arius Satoni Kurniawansyah (Universitas Asahan, 2019)
Abstract - Tabot culture has become a routine ritual of the city of Bengkulu. In addition, the Tabot event can also attract tourists to visit the city of Bengkulu. An ad can be said to be of quality if the ad is able to convey the contents of the advertisement to its customers. Because of the promotion needs, business actors make advertisements so that consumers are interested in using their products. Consumers can capture the contents of the ad if they want to follow and listen carefully, for that we as people in the world of multimedia must be able to make an ad that promotes the product or service with packaging that is attractive and easy to understand by consumers, so consumers are not bored first see the article before the ad is delivered. Then the quality of an advertisement is very influential on the quality of marketing of its products or services. If an advertisement is packaged as attractive as possible, the consumer can be interested and can easily respond to the message content of the ad. So that the producer can take the hearts of consumers and finally the product or service advertised will get a position in the hearts of consumers that will have an impact on the expected marketing results. On 1 to 10 Muharram H (Arabic Calendar) every year in the city of Bengkulu the Tabot Festival is held. The Tabot Festival is held based on the Tabot Cultural Party held by the people of Bengkulu City in commemoration of the death of Amir Hussain, the grandson of Prophet Muhammad SAW, in Padang Karbala (Iraq). This Tabot culture has become a routine ritual of the city of Bengkulu. In addition, the Tabot event can also attract tourists to visit the city of Bengkulu Abstrak - Budaya Tabot telah menjadi suatu ritual rutin masyarakat kota Bengkulu. Selain itu Acara tabot juga dapat menarik wisatawan untuk berkunjung ke kota Bengkulu. Sebuah iklan dapat dikatakan berkualitas jika iklan tersebut mampu menyampaikan isi dari iklan tersebut kepada para konsumennya. Karena kebutuhan promosi maka para pelaku dunia bisnis membuat iklan agar para konsumen tertarik menggunakan produknya. Para konsumen bisa menangkap isi iklan jika mereka mau mengikuti dan menyimak dengan seksama, untuk itu kita sebagai orang yang berkecimpung di dunia multimedia harus mampu membuat sebuah iklan yang mempromosikan yang menarik dan mudah dipahami konsumen, sehingga konsumen tidak bosan terlebih dahulu melihat ikaln tersebut sebelum iklan selesai disampaikan. Maka kualitas suatu iklan sangat berpengaruh terhadap kualitas pemasaran produk atau jasanya. Jika suatu iklan dikemas dengan semenarik mungkin maka konsumen itu dapat tertarik dan bisa merespon isi pesan dari iklan tersebut dengan mudah. Sehingga pihak produsen bisa mengambil hati para konsumen dan akhirnya produk atau jasa yang di iklankan akan mendapat posisi di hati para konsumen yang akan berdampak pada hasil pemasaran yang diharapkan. Budaya Tabot ini telah menjadi suatu ritual rutin masyarakat kota Bengkulu. Selain itu Acara tabot juga dapat menarik para pengunjung yang datang ke kota Bengkulu.